Bio-PCR based diagnosis of Xanthomonas campestris pathovars in black rot infected leaves of crucifers - SINGH, DINESH; DHAR, SHRI (Indian Phytopathology, 2011)
Xanthomonas campestris pv campestris caused black rot disease of crucifers occurs worldwide and causes substantial losses under favorable conditions. A bio-PCR based method has been standardized for the rapid and reliable diagnosis of the black rot disease in crucifers. Primers were used specifically to amplify a 619bp fragment of the hrpF gene from X. campestris. To test specificity of primers, DNA of X. campestris pv. campestris, and other species of Xanthomonas such as X. oryzae pv. oryzae, X. citri pv. citri, X. axonopodis pv. punicae, Erwinia carotovora subsp. carotovora, Pseudomonas fluorescens and P. syringae pv. phaseolicola were also used as template for amplification at 619 bp. For diagnosis, samples of suspected black rot infected leaves of mustard, sarson sag, cauliflower, cabbage, broccoli and radish were collected and isolated bacteria on nutrient agar medium. The colonies of bacteria grown on the medium were used as template for PCR and the same colonies were inoculated to their respective hosts for pathogenicity test. Amplification at 619 bp was visible in all isolates of X. campestris pv. campestris and no amplification was noted with other species of Xanthomonas, Erwinia and Pseudomonas. The colonies amplified at 619 bp were able to produce the symptoms on their respective hosts. There was no amplification in radish sample. It shows that the bio- PCR is confirmatory to the pathogen X. campestris pv. campestris, which rapidly diagnose the disease within 3 - 4 days with great accuracy.